The Effectiveness of Cloud Simacreditation as A Supplement Instrument for Accreditation Value Conversion (ISK) (Case Study: University of Lancang Kuning) - Bayu Febriadi; Febrizal Alfarasy Syam; Pandu Pratama Putra; Ahmad Zamsuri (IJISTECH (International Journal of Information System and Technology), 2022)
SIM Accreditation Cloud is a media accreditation simulation facility that is used by the Study Program and BPM in implementing and monitoring the feasibility of the study program whether it is in accordance with the standards that should be in creating a quality culture. Lancang Kuning University has 21 Study Programs consisting of 9 Faculties, in implementing an internal quality assurance system, Lancang Kuning University has a Quality Assurance Agency in charge of managing a quality culture, but in the implementation of accreditation with IAPS 4.0 this has not been effective, this is proven to be absent from the study program. who are ready to apply with IAPS 4.0, because there are still obstacles in the preparation of accreditation instruments, while the need for accreditation ratings is very much needed by study programs so that they are able to compete and realize the vision and mission of the study program. Sim Akreditasi Cloud 0.7776 koefesien Berpengaruh terhadap nilai instrumen Suplemen Konversi (ISK).